1998
DOI: 10.1111/j.1532-5415.1998.tb02720.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Correlates of Resident Agitation in Alzheimer's Disease Special Care Units

Abstract: While the prevalence of agitation tends to increase as Alzheimer's disease progresses, modifiable treatment factors appear to have a strong influence on the prevalence of agitation. Both physical design and staff treatment appear to influence agitation rates, as do some measures consistent with a low stimulus approach to Alzheimer's care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
112
3
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(121 citation statements)
references
References 32 publications
3
112
3
3
Order By: Relevance
“…These issues can be attributed to: (1) methodological challenges (e.g. small samples, types of setting, measurement of relevant outcomes and environmental features) (Kovach et al, 1997;Gitlin et al, 2003); (2) lack of discernment between the effect of environment and of staff treatment activities (Sloane et al, 1998); and 3) lack of consideration of the different stages of the disease, especially the final stage (Fleming and Purandare, 2010). For these reasons, and although, progress has been made during the last 30 years (Calkins, 2009), evidence on environmental strategies ability to impact positively on patients' outcomes requires further work (Gitlin et al, 2003;Fleming and Purandare, 2010 Most of the criteria or principles, considered in the above tools, are general and do not allow evaluation of specific impact and of the value of different interventions.…”
Section: Indirect Costsmentioning
confidence: 99%
“…These issues can be attributed to: (1) methodological challenges (e.g. small samples, types of setting, measurement of relevant outcomes and environmental features) (Kovach et al, 1997;Gitlin et al, 2003); (2) lack of discernment between the effect of environment and of staff treatment activities (Sloane et al, 1998); and 3) lack of consideration of the different stages of the disease, especially the final stage (Fleming and Purandare, 2010). For these reasons, and although, progress has been made during the last 30 years (Calkins, 2009), evidence on environmental strategies ability to impact positively on patients' outcomes requires further work (Gitlin et al, 2003;Fleming and Purandare, 2010 Most of the criteria or principles, considered in the above tools, are general and do not allow evaluation of specific impact and of the value of different interventions.…”
Section: Indirect Costsmentioning
confidence: 99%
“…However, when taken in conjunction with earlier research, these findings lead to a very mixed picture of SCUs' performance. There are documented differences in quality among SCUs, 32 but the available evidence, to which this research contributes, demonstrates no clear superiority of SCUs over traditional units in either their outcomes or their processes of care. …”
mentioning
confidence: 99%
“…31 Other research has indicated that differences in quality do exist among SCUs. 32 To ensure that our results reflected patterns of care in the better SCUs, as well as in the "average" SCU, we also estimated our models with the SCU group composed only of residents in higher-quality SCUs. These SCUs were ranked on the Special Care Unit Environmental Quality Scale as being in the top one third of the study SCUs, based both on indicators of environmental quality and on measures focusing on staff-resident interactions.…”
Section: Analysis Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…신경-인지적(neuro-cognitive) (Kiely, Morris, & Algase, 2000), 정신사회적(psychosocial) (Thomas, 1997;Song, 2003), 환경적(environmental) (Conant-Arp & Robinson, 1997;Hussian, 1981;Nelson, 1995;Sloane et al, 1998), 인구학적/개인적(Demograpic/personal) (Algase, Beattie, & Song, 2000;Kiely et al, 2000;Thomas, 1997;Song, 2003) 요소 …”
Section: 치매노인의 배회에 대한 정확한 원인은 알려져 있지 않으나mentioning
confidence: 99%